High frequency hydrogen-terminated diamond MESFET with an fmax of 103GHz. (September 2021) - Yu, C.; He, Z.Z.; Zhou, C.J.; Guo, J.C.; Song, X.B.; Cai, S.J.; Feng, Z.H.
Graphical abstract: Abstract: High-quality polycrystalline diamond substrate was used to fabricate diamond MESFETs by a self-aligned process. The fabricated diamond MESFETs with a gate length of 130 nm show good direct current and radio frequency performances, with the maximum saturation source-drain current I DS of 560 mA/mm, the I on / I off ratio of 10 7, the transconductance of 225 mS/mm, and the current gain cut-off frequency f T of 40.7 GHz and the maximum oscillation frequency f max of 103 GHz. These results show that the high-quality polycrystalline freestanding diamond is a promising candidate for the investigation of high frequency electronic devices.